The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13071-016-1946-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synthetic floral-based attractants and sugar baits to capture male and female Aedes aegypti (Diptera: Culicidae)

Abstract: Background: The viruses transmitted by Aedes aegypti, including dengue and Zika viruses, are rapidly expanding in geographic range and as a threat to public health. In response, control programs are increasingly turning to the use of sterile insect techniques resulting in a need to trap male Ae. aegypti to monitor the efficacy of the intervention. However, there is a lack of effective and cheap methods for trapping males. Thus, we attempted to exploit the physiological need to obtain energy from sugar feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Early field trials did not show a positive effect of ATSBs on Ae. aegypti [26,27]; however, a recent field trial in Bamako, Mali, showed promising success [31]. The principle barrier to field trial success appears to be the ability to attract Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early field trials did not show a positive effect of ATSBs on Ae. aegypti [26,27]; however, a recent field trial in Bamako, Mali, showed promising success [31]. The principle barrier to field trial success appears to be the ability to attract Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach differs from most ATSB approaches in two important ways. First, we use a device with a dried sugar solution to elicit an ingestion response while other ATSBs typically use liquid sprayed on vegetation [12,15,17,26]. We hypothesize that the device is a key element in the effectiveness of DABS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attractive toxic sugar baits (ATSBs), which utilize a mix of an oral toxin, natural sugars, and floral attractants to lure mosquitoes [33,34], take advantage of the natural propensity of both male and female mosquitoes to sugar feed. ATSBs can be used in outdoor bait stations, indoor bait stations, or can be sprayed directly onto non flowering vegetation [3537].…”
Section: Candidate Toolsmentioning
confidence: 99%
“…aegypti may not be as unusual as thought previously, as support for frequent sugar-feeding in certain environments has been reported [27,28], and this propensity has been used to design attractive toxic sugar baits for Ae. aegypti control [29,30]. Like larvae, adult mosquitoes may also be in uenced by nutritional stress derived from changes in food quality (e.g., sugar concentration [31]).…”
Section: Introductionmentioning
confidence: 99%